Inovasi Pelayanan Publik Pemerintah Kota Bekasi dalam Bentuk Kebijakan Mal Pelayanan Publik - Zinsky, Winda Purnama; Rusli, Budiman; Bekti, Herijanto (Universitas Medan Area, 2024)
The purpose of this paper is to analyze the Bekasi City Government's Public Service Innovation in the form of the Public Service Mall Policy and describe the inhibiting and supporting factors in the process of public service innovation in Bekasi City. This research uses descriptive qualitative research methods using Rogers' Theory where there are several attributes as a characteristic of an innovation, namely Relative Advantage, Suitability, Complexity, Probability of Experimentation, and Observability. The results showed that the Public Service Mall in Bekasi City has become a significant innovative solution in the delivery of public services in Indonesia, especially in Bekasi City. because the Public Service Mall concept offers an integrated, efficient, and more responsive approach to the needs of the community in accessing various public services in one place.